Arsenic mineralogy and distribution at the historic Alexander gold mine, Reefton goldfield, New Zealand. Issue 2 (3rd April 2017) - Malloch, Kirstine R.; Craw, Dave; Trumm, Dave
ABSTRACT: A processing complex consisting of two sites adjacent to the Alexander River was developed prior to the 1950s for the Alexander orogenic gold mine on the West Coast of New Zealand. The mineralogy of the As has been defined at both sites, in order to evaluate potential environmental toxicity. Arsenic levels are highest (> 35 wt%) where the ore had been roasted, converting sulfides to arsenolite (As(III)2 O3 ), which is soluble in the wet environment. High As levels elsewhere on the processing complex occur as secondary As(V)–Fe(III)–Ca minerals, including pharmacolite and yukonite, and As-bearing hematite. Sulfide concentrates stored on-site have oxidised to semi-cemented amorphous hydrous Fe(III) oxides and arsenates, resulting in localised acid generation (pH as low as 3) and As levels up to 4 wt%. Despite high levels of As in the processing residues and the wet climate, negligible As is being mobilised into stream waters, and the dissolved As level is < 0.01 mg/L.